CO2, nitrogen deposition and a discontinuous climate response drive water use efficiency in global forests - Mark A. Adams (Nature Portfolio, 2021)
Water use efficiency is a key measure of plant responses to climate change. Here, the authors investigate its control by CO2, nitrogen deposition, and water availability using a global tree-ring dataset. They find an aridity threshold and quantify changes in control over the past 50 years.